Implementasi Model Pembelajaran PjBL Berbantuan Media Wordwall terhadap Hasil Belajar pada Materi Laju Reaksi - Jesika Silaban; Nurfajriani Nurfajriani (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
Low student chemistry learning outcomes, particularly in the abstract topic of reaction rates, coupled with teacher-dominated learning, are among the problems that need to be addressed through the application of innovative learning models and media. This study aims to determine the improvement in chemistry learning outcomes of eleventh-grade high school students on reaction rates after the implementation of the Project Based Learning (PjBL) model assisted by Wordwall. This study used a quasi-experimental method with a nonequivalent control group design. The sample consisted of two eleventh-grade high school classes determined using a purposive sampling technique: the experimental class and the control class. The research instrument used was a validated multiple-choice learning outcome test. The results showed a significant increase in learning outcomes (N-Gain 0.7638) in the high category in the experimental class, with a statistically significant difference (p < 0.05) compared to the control class. The application of the PjBL model assisted by Wordwall has the potential to increase student interest and learning outcomes in reaction rates compared to conventional learning.